La profesionalización del cuidado durante el ordenamiento estatal: maestras y enfermeras en la provincia de Río Negro (Argentina) : The professionalization of care during state orders: teachers and nurses in the province of Río Negro (Argentina) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
The incorporation of Patagonia into the national state was late and uneven, marked by a slow and uneven institutionalization from the late 19th century until the 1930s. Following the military coup of 1930, the dictatorial government promoted the nationalization of the territory, reinforcing state control and deploying a civilizing project based on order, discipline, and work. During the 1930s and 1940s, this state presence intensified through infrastructure development, the deployment of civil servants, and the expansion of educational and health institutions. Within this framework, both during the territorial period and in the early years of the provincialization of Río Negro (1955 onward), policies aimed at professionalizing two key figures in shaping the social order were promoted: teachers and nurses.This article aims to analyze, from a gender perspective, the career trajectories of these women engaged in caregiving and working in schools and health institutions. We focus on the authority relations, prescriptive discourses, and normative expectations that structured their work to explain the place teachers and nurses occupied in state projects and the ways their roles were shaped by values ​​linked to vocation, morality, and self-sacrifice.